Use of diallyl disulphide for the commercial control of Sclerotium cepivorum - Tyson, J.L.; Fullerton, R.A.; Elliott, G.S.; Reynolds, P.J. (New Zealand Plant Protection, 2000)
Soil treatment with diallyl disulphide (DADS) for the control of Allium white rot (Sclerotium cepivorum Berk) was studied in two trials under commercial growing conditions In the 19961998 trial two applications of DADS gave a 79 increase in yield when compared with the untreated control; the addition of three tebuconazole applications gave no extra yield One application of DADS gave a 33 increase in yield In the 19982000 trial various DADS application rates were tested All DADS treatments resulted in a large reduction in Allium white rot incidence compared with the untreated control Application of DADS gave a 57 increase in yield relative to the untreated control